Pengaruh Model Creative Problem Solving (Cps) Terhadap Hasil Belajar Pendidikan Agama Islam (PAI) Siswa Kelas V SDN Kecamatan Pakem, Kabupaten Bondowoso - Sutiana Sutiana; Haya Haya; Mundzir Mundzir (Pusat Riset dan Inovasi Nasional, 2022)
This research aims to describe the influence of the implementation of Creative Problem Solving learning on PAI learning outcomes. This research is a quasi-experiment with a research design using a posttest only control group design. The research population was 401 grade V students at PAKEM District Elementary School. The sample consisted of 120 students who were divided into two experimental classes and two control classes using group random sampling technique. The instrument used is the PAI learning outcomes questionnaire. Data analysis was carried out using ANOVA. The results of this research show that: a) there is a difference in social studies learning outcomes between students who take part in Creative Problem Solving learning and students who take part in conventional learning with a Fhit value of 22.284 > Ftab (3.93), b) there is an influence between the application of creative problem solving learning and multicultural attitudes towards PAI learning outcomes with a Fhit value of 66.428 < Ftab (3.97).